Overwiev of invasion and control management options of Cydalima perspectalis (Lepidoptera, Crambidae) (Journal of Forestry, 2025)
The box tree moth, Cydalima perspectalis, originally from East Asia, is now a widespread pest found in three continents. It has invaded 40 countries in Europe and the Middle East, as well as two countries in North America. The exact pathway of invasion is uncertain, but it is believed to have reached Europe and the United States through the import boxwood plants. This review aims to provide an overview of the highly invasive C. perspectalis, and identify perspectives for its effective control and management. The spread of C. perspectalis is due to multiple introductions, biological characteristics of the species, and the wide distribution of the host plant. Its distribution in Europe indicates it is well-established, and climate models predict further damage in southern and central Europe. In North America, more knowledge is needed for effective monitoring and management. Climatic conditions and host plant susceptibility play a significant role in the invasion process. Control methods include insecticides and environmentally friendly options such as entomopathogenic bacterial strains, fungi, nematodes, plant insecticides, and disruption of mating. A multidimensional approach is crucial for the management and control of the C. perspectalis. Improving detection methods, implementing prevention strategies, monitoring seasonal fluctuations and damage, assessing overwintering capacity, and developing effective control measures are key future perspectives. Through research, collaboration, and strategic interventions, it is possible to mitigate the impact of C. perspectalis and protect vulnerable ecosystems from the devastating consequences of this invasive pest.